Phytotoxicity Analysis of Untreated and Bacterial Consortium Treated Textile Dye Effluent - Karthikeyan, K (International Journal of Pharmaceutical & Biological Archive, 2015)
Phytotoxicity Analysis of Untreated and Bacterial Consortium Treated Textile Dye Effluent